Flora Fauna Biodiversity and CSR Implementation in the Mangrove Ecosystem of Bagan Serdang Village, North Sumatra Province. - Ahmad Muhtadi; Rusdi Leidonald; Kamto Triwibowo; Nurul Azmi (Faculty of Fisheries and Marine Universitas Airlangga, 2020)
HighlightsMangrove sampling was conducted to use the